From Tucuman to Peru: The reparto and trade of mules in the second half of the 18th century - Bebin Cúneo, Sergio (2022)
This research focuses on mules, mammals whose strength and endurance were essential to the Spanish-American colonial economy at a time when there were no tractors or railways. The study explores the importance of mules for overland trade, the difficulties and risks faced by mule traders, the credit problems of the Indians and the development of the reparto system that simplified business. Both registers and testimonies in Peru show a severe shortage of mules as a result of the suppression of the reparto system, decreed by the Crown since 1780. Faced with this major problem, authorities and traders tried to reverse the situation.